Toxicokinetics of Arenobufagin and its Cardiotoxicity Mechanism Exploration Based on Lipidomics and Proteomics Approaches in Rats - Zhao, Lijuan; Han, Lingyu; Wei, Xiaolu; Zhou, Yanyan; Zhang, Yanqiong; Si, Nan; Wang, Hongjie; Yang, Jian; Bian, Baolin; Zhao, Haiyu (Frontiers in Pharmacology, 2021)
Arenobufagin (ArBu), one of the main active bufadienolides of toad venom with cardiotonic effect, analgesic effect, and outstanding anti-tumor potentiality, is also a potential cardiotoxic component. In the present study, the cardiac effect of ArBu and its underlying mechanism were explored by integrating data such as heart rates, toxicokinetics, myocardial enzyme and brain natriuretic peptide (BNP) activity, pathological sections, lipidomics and proteomics. Under different doses, the cardiac effects turned out to be different. The oral dose of 60 mg/kg of ArBu sped up the heart rate. However, 120 mg/kg ArBu mainly reduced the heart rate. Over time, they all returned to normal, consisting of the trend of ArBu concentration-time curve. High concentrations of myocardial enzymes and BNP indicated that ArBu inhibited or impaired the cardiac function of rats. Pathological sections of hearts also showed that ArBu caused myocardial fiber disorder and rupture, in which the high-dose group was more serious. At the same time, serum and heart tissue lipidomics were used to explore the changes in body lipid metabolism under different doses. The data indicated a larger difference in the high-dose ArBu group. There were likewise many significant differences in the proteomics of the heart. Furthermore, a multi-layered network was used to integrate the above information to explore the potential mechanism. Finally, 4 proteins that were shown to be significantly and differentially expressed were validated by targeted proteomics using parallel reaction monitoring (PRM) analysis. Our findings indicated that ArBu behaved as a bidirectional regulation of the heart. The potential mechanism of cardiac action was revealed with the increased dose, which provided a useful reference for the safety of clinical application of ArBu.